Multiple Time-Point 68Ga-PSMA I&T PET/CT for Characterization of Primary Prostate Cancer: Value of Early Dynamic and Delayed Imaging. (June 2017) - Schmuck, Sebastian; Mamach, Martin; Wilke, Florian; von Klot, Christoph A.; Henkenberens, Christoph; Thackeray, James T.; Sohns, Jan M.; Geworski, Lilli; Ross, Tobias L.; Wester, Hans-Juergen; Christiansen, Hans; Bengel, Frank M.; et al.
Abstract : Purpose: The aims of this study were to gain mechanistic insights into prostate cancer biology using dynamic imaging and to evaluate the usefulness of multiple time-point 68 Ga–prostate-specific membrane antigen (PSMA) I&T PET/CT for the assessment of primary prostate cancer before prostatectomy. Methods: Twenty patients with prostate cancer underwent 68 Ga-PSMA I&T PET/CT before prostatectomy. The PET protocol consisted of early dynamic pelvic imaging, followed by static scans at 60 and 180 minutes postinjection (p.i.). SUVs, time-activity curves, quantitative analysis based on a 2-tissue compartment model, Patlak analysis, histopathology, and Gleason grading were compared between prostate cancer and benign prostate gland. Results: Primary tumors were identified on both early dynamic and delayed imaging in 95% of patients. Tracer uptake was significantly higher in prostate cancer compared with benign prostate tissue at any time point ( P ⩽ 0.0003) and increased over time. Consequently, the tumor-to-nontumor ratio within the prostate gland improved over time (2.8 at 10 minutes vs 17.1 at 180 minutes p.i.). Tracer uptake at both 60 and 180 minutes p.i. was significantly higher in patients with higher Gleason scores ( P < 0.01). The influx rate ( K i ) was higher in prostate cancer than in reference prostate gland (0.055 [ r = 0.998] vs 0.017 [ r = 0.996]). Conclusions: Primary prostate cancer is readily identified on early dynamic and static delayed 68 Ga-PSMA ligand PET images. The tumor-to-nontumor ratio in the prostate gland improves over time, supporting a role of delayed imaging for optimal visualization of prostate cancer.